Third-generation wireless must wait for services to catch up. - Oliphant, M.W (IEEE spectrum)
3G is all about new services and content to keep the wireless party going. Like cable TV companies of yore, cellular operators today are awaiting the arrival of smashing new content to generate new streams of revenue as they build a new and expensive third-generation global network. Coming in two flavors (cdma2000 and UMTS/WCDMA), 3G technologies serve largely to protect the investment of their second-generation predecessors: IS-95, and GSM/IS-136, respectively. The amazing success of 2G digital cellular is proof that there is nothing wrong with today's networks. So, why build new ones? Basically, so that operators' efforts to find new sources of revenue will not be limited by market saturation. Cable TV experience proves that subscribers care little about networks and technologies; they just want new stuff. Like cable network providers before them, wireless network providers will not have to create the new services themselves. Rather, they will have to give the content providers virtual control over the network's bandwidth, allowing them to use what they need. What both content providers and network operators must ensure is that the right amount of bandwidth is assigned to bits according to the value perceived by subscribers. It will be up to the content providers to make the bits more valuable than ever before.